Tinjauan Persepsi dan Analisis Sentimen Mahasiswa Dalam Implementasi Program Merdeka Belajar Kampus Merdeka - Rinda Cahyana; Annas Nurul Hakim; Fajar Al-Husein; Deni Wildan Munawar (Puslitbang Akademi Relawan TIK Indonesia, 2026)
The Independent Learning Campus (MBKM) program is a higher education initiative that provides students with learning freedom and practical experience. However, its implementation still faces challenges, particularly related to low student participation rates, despite positive sentiment toward the program. This study aims to systematically review the literature discussing student perceptions and sentiments regarding their decision to participate in the MBKM program. The method used was a literature review of various scientific publications that examine survey approaches and sentiment analysis using machine learning algorithms. The review results indicate that the main obstacles influencing student decisions include a lack of socialization, limited infrastructure, and a lack of technical understanding related to the program. This study concludes that the integration of survey approaches and digital data analysis has the potential to strengthen understanding of the factors influencing student participation and provide a basis for more responsive and data-driven MBKM policy-making.